2020
DOI: 10.3390/s20247192
|View full text |Cite
|
Sign up to set email alerts
|

Retrieval of Hyperspectral Information from Multispectral Data for Perennial Ryegrass Biomass Estimation

Abstract: The use of spectral data is seen as a fast and non-destructive method capable of monitoring pasture biomass. Although there is great potential in this technique, both end users and sensor manufacturers are uncertain about the necessary sensor specifications and achievable accuracies in an operational scenario. This study presents a straightforward parametric method able to accurately retrieve the hyperspectral signature of perennial ryegrass (Lolium perenne) canopies from multispectral data collected within a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“…Since plant height is easy to measure and extract from inexpensive sensors/cameras, the current trend of developing prediction models is based on the combination of plant height with other parameters (like VIs). While the VIs remain the fixed limitation, the main improvement of model accuracy is therefore depended on the plant height capacity (Togeiro de Alckmin et al, 2021). Many studies showed that higher accuracy of plant height was measured by being closer to the ground level than aerial cameras (Madec et al, 2017;Wang et al, 2018;Yuan et al, 2018a).…”
Section: Discussionmentioning
confidence: 99%
“…Since plant height is easy to measure and extract from inexpensive sensors/cameras, the current trend of developing prediction models is based on the combination of plant height with other parameters (like VIs). While the VIs remain the fixed limitation, the main improvement of model accuracy is therefore depended on the plant height capacity (Togeiro de Alckmin et al, 2021). Many studies showed that higher accuracy of plant height was measured by being closer to the ground level than aerial cameras (Madec et al, 2017;Wang et al, 2018;Yuan et al, 2018a).…”
Section: Discussionmentioning
confidence: 99%